Nali al-Shahrazouri's creed opinions on prophecies Analytical research (Raparin Journal of Humanities (RJH), 2023)
Throughout the history of the Kurds, we have had many scholars and writers whose peers are few among the Kurds. Among them, a poet by the name of Mullah Khader—nicknamed Nali—rose to appearance. More significantly, he has been recognized as one of the primary figures in the development of Kurdish literature written in the Sorani dialect in the nineteenth century and the Kurdish classical poetry school. Therefore, as part of our accountability, we performed an excellent research of the terminology and idioms employed in his book by scholars and theologians. After many years, we no longer see writers and academics among the Kurds and other nearby nations caring for his literary works. As a result, we are carrying out this tremendous and historic duty in compliance with our religious and literary responsibilities. There is no doubt that in light of his being influenced by his readings of Arabic and Persian literature, which are rich in theological and religious subjects, including dogmas, he composed many poems against doctrinal and theological issues, including the prophetic aspect, issues of prophecy and the message, his view of the prophets and messengers, not to mention the hadith of the prophecy of our master Muhammad (PBUH), his understanding of it in The miracle, which motivated him more to compose many verses about this chapter and put them in his collection, is reflected in the strength of his strong faith, cultural and intellectual ties that he drew from the luminaries of the Holy Qur’an and the Prophetic hadiths (PBUH). So; We seek, through this study, to know the extent to which he was affected by the faith, as well as to add high-end knowledge to the product of the Kurdish people's thought about one of their most prominent poets, and to answer many questions about what is raised about the literature related to faith and important verbal references. We realized that he was an inspiring poet and a man of knowledge in this field, and he had the upper hand in how to select the doctrinal and verbal terms and their consistency in a verse, even on several occasions, he fell into purely verbal discussions with his peers. It is worth noting that the study included two main topics and several demands, with reference to the most important results that we reached. By God, we ask that we were able to add new information, even by a line, to the history of our Kurdish thought.